2020
DOI: 10.2340/00015555-3459
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction and Expectations Regarding Mobile Teledermoscopy in General Practice for Diagnosis of Non-melanoma Skin Cancer and Malignant Melanoma

Abstract: Mobile teledermoscopy enables enlarged photographs of suspicious skin changes to be taken in general practice and sent for evaluation by a specialist. Patient satisfaction and expectations regarding this new diagnostic method need to be evaluated before implementation. The aim of this cross-sectional study was to evaluate patient satisfaction and expectations regarding mobile teledermoscopy, and to identify factors influencing patient satisfaction and choice of diagnostic method. A total of 287 out of 476 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…Finally, patients were highly satisfied with the TELESPOT project (global satisfaction: 8.8/ 10), although use of telemedicine and teledermatology is not yet part of their daily life in Belgium. Our results are in line with other studies reporting patient satisfaction levels of 58.5% [16].…”
Section: Discussionsupporting
confidence: 93%
“…Finally, patients were highly satisfied with the TELESPOT project (global satisfaction: 8.8/ 10), although use of telemedicine and teledermatology is not yet part of their daily life in Belgium. Our results are in line with other studies reporting patient satisfaction levels of 58.5% [16].…”
Section: Discussionsupporting
confidence: 93%
“…Satisfaction of both patient and provider is believed to be an important factor in the successful implementation of novel technologies [8,9]. We previously reported that almost 90% of patients were satisfied with, or neutral towards, the use of teledermoscopy [10].…”
Section: Introductionmentioning
confidence: 99%
“…10,26 Teledermoscopy appears to effectively triage 'spot checks', sending the most concerning lesions to be seen in-person quickly, while reassuring clearly benign lesions that might allow patients to avoid an in-person encounter altogether. [35][36][37][38][39] For those patients without ready access to a dermatologist due to financial or geographic limitation, teledermoscopy may afford the only opportunity for early detection of cutaneous malignancies. 40,41 A recent study by Sangeeta et al in 2019 compared the effectiveness of FTF workflows with teledermoscopy in the diagnosis of skin cancer.…”
Section: Teledermoscopy and Skin Cancer Detectionmentioning
confidence: 99%